Antibacterial activity and shear bond strength of fiber-reinforced composites and bonding agents containing 0.5%, 1%, 2.5%, and 5% silver nanoparticles - Nastaran Jenabi; Susan Sadeghian; Fathallah Karimzadeh; Maryam Safavi Pour; Vahid Rakhshan (Wolters Kluwer Medknow Publications, 2023)
Background: Bonded composites may increase bacterial accumulation and caries formation risk. Therefore, assessment of methods to decrease bacterial activity around them would be valuable. The literature on the efficacy of adding silver nanoparticles to fiber-reinforced composite (FRC) or adding them to bonding agents in terms of their antibacterial activity and/or shear bond strength (SBS) is scarce. Thus, we aimed to assess the antibacterial activity of flowable composites and bonding agents containing various percentages of experimental silver nanoparticles (nanosilver) against S. mutans and to evaluate the SBS of FRC and bonding agents containing different amounts of nanosilver to enamel. Materials and Methods: In this preliminary study, 0% (control), 0.5%, 1%, 2.5%, and 5% nanosilver were added to flowable composite and bonding agent. Syntheses of nanosilver and nanosilver-incorporated composite specimens were approved using X-ray diffraction spectroscopy and scanning electron microscopy. Antibacterial effects of the produced materials on S. mutans were evaluated by colony count with serial dilution method (n = 7 groups × 10 [n = 70] specimens) and agar disc diffusion test (n = 6 groups × 5 [n = 30] composite specimens + n = 6 groups × 5 [n = 30] light-cured bonding + n = 6 groups × 5 [n = 30] uncured bonding) against negative control and cefotaxime antibiotic. Moreover, SBS values of various FRC blocks bonded to enamel using various bonding agents were measured (n = 9 groups × 6 [n = 54] human premolars). Data were analyzed using Kruskal-Wallis, Dunn, two-way analysis of variance, and Tukey's tests (α = 0.05). Results: Composite discs containing all concentrations of nanosilver reduced S. mutans colony counts (P < 0.05); bacterial growth was ceased at samples containing 2.5% and 5% of nanosilver. The reduction in the SBS of FRCs was significant only for 5% nanosilver (P < 0.05). Conclusion: Adding 0.5%, 1%, and 2.5% nanosilver to composite and 0.5% or 1% nanosilver to bonding agent led to a significant antibacterial behavior against S. mutans while not significantly affecting the SBS of FRC.